An alternative estimate of Canadian potential output: The multivariate state-space framework - Lise Pichette; Maria Bernier; Marie-Noëlle Robitaille (Bank of Canada, 2018)
In this paper, we extend the state-space methodology proposed by Blagrave et al. (2015) and decompose Canadian potential output into trend labour productivity and trend labour input. As in Blagrave et al. (2015), we include output growth and inflation expectations from consensus forecasts to help refine our estimates. Our alternative model, which we call the multivariate state-space framework (MSSF), adds to the Bank's existing set of tools for estimating potential output and the output gap in Canada. We find that while the MSSF shares similar dynamics to the main approaches used by the Bank, it also indicates that the economy experienced greater excess supply in both the 1990 and 2008 recessions than the Bank's other tools would suggest. Finally, the MSSF estimates that the Canadian economy has been operating close to capacity since the end of 2017.
Keywords: C5; E0; E5; 330; Economic models; Potential output